2021
DOI: 10.1093/eurjpc/zwab067
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk stratification by coronary computed tomography angiography imaging: current state-of-the-art

Abstract: Current cardiovascular risk stratification by use of clinical risk score systems or plasma biomarkers is good but less than satisfactory in identifying patients at residual risk for coronary events. Recent clinical evidence puts now further emphasis on the role of coronary anatomy assessment by coronary computed tomography angiography (CCTA) for the management of patients with stable ischaemic heart disease. Available computed tomography (CT) technology allows the quantification of plaque burden, identificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 130 publications
0
19
2
1
Order By: Relevance
“…In recent years, the pericoronary fat attenuation index (FAI), which is measured using coronary CT angiography (CCTA) images, can be used to reflect pericoronary inflammation [2,3]. Recent studies have shown that pericoronary adipose tissue (PCAT) participates in the process of coronary inflammation and is significantly related to the type of plaque and degree of stenosis [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the pericoronary fat attenuation index (FAI), which is measured using coronary CT angiography (CCTA) images, can be used to reflect pericoronary inflammation [2,3]. Recent studies have shown that pericoronary adipose tissue (PCAT) participates in the process of coronary inflammation and is significantly related to the type of plaque and degree of stenosis [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The amalgam of anatomical, functional and biological information accrued by CCTA offers a multifaceted risk stratification of patients for targeted prevention strategies. 58 …”
Section: Discussionmentioning
confidence: 99%
“…The most notorious HRP feature is the NRS, which is currently considered the CCTA hallmark of the vulnerable atherosclerotic plaque [ 84 ]. Studies employing CCTA and intracoronary imaging have shown that the NRS is predominantly found in high-risk lesions such as in thin cap fibroatheroma (44% vs. only 4% in non-thin cap fibroatheroma).…”
Section: Coronary Computed Tomography Angiographymentioning
confidence: 99%